CHILD GROOMING CRIMINAL REGULATIONS IN THE NATIONAL CRIMINAL CODE - An’nissa Sukmaningrum; Lilis Suryani; Ardiyanti Aris; Kairuddin; Muhammad Darwis (PT. Radja Intercontinental Publishing, 2026)
The development of information technology has transformed patterns of social interaction and digital communication, leading to the emergence of various forms of sexual crimes against children, one of which is child grooming. This crime is committed through a process of approaching, psychologically manipulating, and building trust with a child for sexual exploitation. This study aims to analyze the regulation of the criminal offense of child grooming under the national Criminal Code (KUHP) and to examine the limitations of its legal framework. This research is a normative legal study employing both statutory and conceptual approaches. The legal materials used consist of primary, secondary, and tertiary sources, which are analyzed qualitatively. The findings indicate that child grooming has not yet been explicitly regulated as a distinct criminal offense under the national Criminal Code. However, in substance, it has been implicitly accommodated through Article 417, which regulates acts of giving or promising gifts, abusing authority or influence, and deceiving a child for sexual purposes. The study also finds that this regulation remains limited because Article 417 is constructed as a material offense, does not fully address the characteristics of digital-based child grooming, and fails to accommodate the process of psychological manipulation at the initial stage before sexual exploitation occurs. Therefore, a more adaptive reform of criminal law is required to provide legal certainty regarding the criminal offense of child entrustment.